2018
DOI: 10.1182/blood-2017-12-822569
|View full text |Cite|
|
Sign up to set email alerts
|

Improving CLL Vγ9Vδ2-T–cell fitness for cellular therapy by ex vivo activation and ibrutinib

Abstract: The efficacy of autologous (αβ) T-cell-based treatment strategies in chronic lymphocytic leukemia (CLL) has been modest. The Vγ9Vδ2-T cell subset consists of cytotoxic T lymphocytes with potent antilymphoma activity via a major histocompatibility complex-independent mechanism. We studied whether Vγ9Vδ2-T cells can be exploited as autologous effector lymphocytes in CLL. Healthy control Vγ9Vδ2-T cells were activated by and had potent cytolytic activity against CLL cells. However, CLL-derived Vγ9Vδ2-T cells prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 65 publications
1
67
0
Order By: Relevance
“…Several studies have demonstrated that standard chemotherapeutic drugs or kinase inhibitors frequently increase the cancer cell susceptibility to γδ T cell killing, for instance, for colon cancer, 208 glioblastoma, 209 ovarian cancer, 210 or chronic lymphocytic leukemia. 211 Thus, relevant preclinical model systems suggest synergistic effects of combined chemotherapy and adoptive transfer of allogeneic Vδ2T cells. 210 A large number of substances have been shown to epigenetically modify gene expression at the level of DNA methylation and histone modification, and several drugs, including the histone deacetylase inhibitor valproic acid (VPA) and the DNA demethylating agent decitabine, are clinically used.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…Several studies have demonstrated that standard chemotherapeutic drugs or kinase inhibitors frequently increase the cancer cell susceptibility to γδ T cell killing, for instance, for colon cancer, 208 glioblastoma, 209 ovarian cancer, 210 or chronic lymphocytic leukemia. 211 Thus, relevant preclinical model systems suggest synergistic effects of combined chemotherapy and adoptive transfer of allogeneic Vδ2T cells. 210 A large number of substances have been shown to epigenetically modify gene expression at the level of DNA methylation and histone modification, and several drugs, including the histone deacetylase inhibitor valproic acid (VPA) and the DNA demethylating agent decitabine, are clinically used.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…The numbers of NK and CD8 1 T cells are relatively low, as well as Vd1 and Vd2 T-cell numbers, both of which have cytotoxic properties against CLL cells. 52,53 Moreover, high PD-1 expression on CD8 1 T cells fits with an immunosuppressed profile in the LN. The increased numbers of T regs in the LN that we and other investigators describe likely suppress cellular immune responses within the LN.…”
Section: Discussionmentioning
confidence: 94%
“…7 Moreover, ibrutinib has been found to help restore host immunity by increasing T cell number and repertoire diversity, improving T cell function, suppressing immunosuppressive molecule ligands such as programmed death-ligand 1 (PD-L1) on cancer cells, and eliminating BTK-expressed myeloid-derived suppressor cells (MDSC). [8][9][10][11][12][13][14] However, ibrutinib also cast negative effects on anti-tumor immunity through promotion of the anti-apoptosis effect of nurse-like cells (NLCs) and inhibition of NLC phagocytic ability by compelling them expressing M2-skewed tumor associated macrophages phenotype. 15 Besides, ibrutinib has been reported to attenuate rituximab-dependent cytotoxicity by targeting ITK in NK cells.…”
Section: Peer Reviewmentioning
confidence: 99%